What's on the Menu? Policies to Reduce Young People's Sugar Consumption. (21st May 2020) - Griffith, Rachel; O'Connell, Martin; Smith, Kate; Stroud, Rebekah
Abstract: Young people in the UK consume far above the maximum recommended levels of added sugar. It is likely that neither they nor their parents fully take account of the future health, social and economic costs of this high sugar consumption. This provides a rationale for policy intervention. The majority of young people's added sugar consumption occurs in the home, where purchases are typically made by parents. This means that understanding the purchase decisions of adults is important for policy design, even if the policies aim to reduce the consumption of young people. We discuss the merits of popular policies, including taxes, advertising restrictions and restrictions on the availability of specific foods, and we identify promising avenues for future research.